Leibnitz's contribution to mind- Body problem in modern Philosophy - A critical analysis based on Monadology - Poologanathan, P. (South Eastern University of Sri Lanka, 2016)
One of the most ancient problems of Philosophy is the problem of the relationship between mind and body. How could mind and body, which are different in nature, active one another? Several philosophers from Greek to the current period have been put forwarding solutions for finding a solution to this problem between mind and body. Descartes separated mind and body and established the dualism. He said that the Pineal Gland is the reason behind the driving of one another by these two things which have natures that are different from one another. Here a problem arises as to how could the pineal gland which is substance in nature, could act the mind which is non substance in nature. Spinoza formulated Pantheism through his Monism principle and said that both body and mind are two natures of God who is a mono thing. Here a question rises as to how the mono thing God could possess two natures? At this stage, modern period philosopher Leibnitz put forwarded his monads principle to find a solution to the mind —body problem in his book Monadology. The objective of this study is to critically analyze whether this principle of Leibnitz constituted a correct solutions to problems regarding body and mind prevailing so far. For this study, analytical and critical methods are used and also data collected from secondary sources.
Keywords: Mind-body; Pantheism; Monism; Monads; Dualism